Comparative muscle activities of the rotational and glide technique in shot put - Aoyama, S.; Aoyama, T.; Tsunoda, N. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: A lot of shot put studies have examined the biomechanics and optimal release conditions, such as release speed, release angle and release height. Although these parameters directly determine the performance, there is no study for same subject of using rotational and glide technique in shot put. Therefore, the purpose of this study was to analysis the muscle activities of trunk and lower limb in shot put of two different technique, especially release-phase, and these differences are able to help determination to coaching. Methods: The subjects were seven male shot put throwers who can use rotational and glide technique (age:22.7±2.3yrs, height:176.6±6.8cm, body weight:107.6±15.1kg, rotational throw:14.1±1.3m, glide throw:13.4±1.5m). All the subjects performed three rotational throws and three glide throws same as a competition rule with recorded best throw from both techniques. Muscle activities were measured by electromyography of trunk (latissimus dorsi muscle, external oblique muscle) and lower limb (vastus lateralis, biceps femoris muscle, adductor muscle gastrocnemius) muscle on right and left, which was calculated of iEMG from EMG. Throwing movements were measured by 3-D analysis that defined by the divided turn-phase and release-phase with two positions. Results: The results of this study were as follows: Muscle activities of the rotational technique in the trunk and lower limb muscle were showed higher iEMG values than the glide technique, and especially external oblique muscle, biceps femoris muscle, right and left adductor muscle and left gastrocnemius of rotational technique were significantly higher than the glide technique (p<0.05). Discussion: In this study, it was a significantly higher iEMG value of left side muscle activities in trunk and lower limb of the rotational technique than the glide technique. These results suggested that the rotational technique is greater eccentric contraction with the left side (leg and trunk) of the release phase than the glide technique, thus this means that the necessary for an effective block action of left side during release phase. In addition, the rotational technique of muscle activities in the left side might be enhanced the accretion of shot during release phase than the glide technique. Therefore, coaches are advised to pay particular attention to the left side muscle during the release phase for the especially rotational technique.